Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by the Substitution Method - Exercise Set - Page 300: 19



Work Step by Step

2x-y=6 2x-2x-y=6-2x -y=6-2x -1(-y)=-1(6-2x) y=-6+2x Plug this value for y into the other equation. 3x+2y=5 3x+2(-6+2x)=5 3x+2(-6)+2(2x)=5 3x-12+4x=5 3x+4x-12=5 7x+12=5 7x+12-12=5+12 7x=17 x=$\frac{17}{7}$ Plug this value for x back into the first equation. y=-6+2($\frac{17}{7}$) y=-6+$\frac{34}{7}$ y=-$\frac{42}{7}$+$\frac{34}{7}$ y=-$\frac{8}{7}$ Therefore the solution is {($\frac{17}{7}$,-$\frac{8}{7}$)}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.